El Ciclotrón como Fundamento de Desarrollo Científico. - Sarta Fuentes, José Antonio (Ingeniería, 1999)
Installation of a cyclotron in Colombia, in order to produce radioisotopes which yield positrons, can be used in medicine, research and analytical techniques which are actually being utilized in Colombia. This paper shows a general review of different methods and some beneficials which can be carried out with a cyclotron in basic and applied researcher. Once the cyclotron will be acquired and commisioned the knowledge related to different areas will be complemented and improved. Aplications related to medicine have not been taken into account.